A hybrid batswarm algorithm for optimizing dam and reservoir operation - Yaseen Z.M.; Allawi M.F.; Karami H.; Ehteram M.; Farzin S.; Ahmed A.N.; Koting S.B.; Mohd N.S.; Jaafar W.Z.B.; Afan H.A.; El-Shafie A. (Springer London, 2023)
Dams; Irrigation; Particle swarm optimization (PSO); Bat algorithms; Global optimal solutions; Hybrid optimization algorithm; Multi-reservoir systems; Optimization algorithms; Optimization modeling; Particle swarm optimization algorithm; Reservoir operation; Reservoirs (water)